2020
DOI: 10.1021/acs.jpclett.0c00758
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Imaging of a Free-Standing Monolayer Clay Mineral Nanosheet Using Scanning Transmission Electron Microscopy

Abstract: Although aberration-corrected scanning transmission electron microscope (STEM) enables the atomic-scale visualization of ultrathin 2D materials such as graphene, imaging of electron-beam sensitive 2D materials with structural complexity is an intricate problem. We here report the first atomic-scale imaging of a free-standing monolayer clay mineral nanosheet via the annular dark field (ADF) STEM. The monolayer clay nanosheet was stably observed under optimal conditions, and we confirmed that the hexagonal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…5 We recently achieved atomic-scale imaging of a freestanding (i.e., without any surfactants or supporting matrices) monolayer clay mineral by annular dark-field (ADF) STEM. 22,24 The monolayer clay mineral was observed at the atomic-scale without any destruction, although bulk clay minerals are generally sensitive to the electron beam irradiation, as reported for cross-sectional imaging at the atomic-scale via (S)TEM. [25][26][27][28][29] In this report, we demonstrate the outstanding stability of freestanding monolayer clay mineral by comparing the decrease of selected area electron diffraction (SAED) intensity against those of the two-or three-layered (2L or 3L) clay mineral.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…5 We recently achieved atomic-scale imaging of a freestanding (i.e., without any surfactants or supporting matrices) monolayer clay mineral by annular dark-field (ADF) STEM. 22,24 The monolayer clay mineral was observed at the atomic-scale without any destruction, although bulk clay minerals are generally sensitive to the electron beam irradiation, as reported for cross-sectional imaging at the atomic-scale via (S)TEM. [25][26][27][28][29] In this report, we demonstrate the outstanding stability of freestanding monolayer clay mineral by comparing the decrease of selected area electron diffraction (SAED) intensity against those of the two-or three-layered (2L or 3L) clay mineral.…”
Section: Introductionmentioning
confidence: 83%
“…[14][15][16][17][18][19][20][21] However, (S)TEM imaging of free-standing monolayer clay minerals, which have a more complicated structure than their preceding few-atom thick materials, such as graphene, at the atomic-scale has not been achieved, except in our recent study. 22 Once non-destructive direct imaging of clay mineral nanosheet or useful clay mineral-based organicinorganic hybrid materials at the atomic scale is established, it will strongly promote their applicability such as selective adsorption for heterogeneous catalyst or sensing, 23 or photoenergy conversion. 5 We recently achieved atomic-scale imaging of a freestanding (i.e., without any surfactants or supporting matrices) monolayer clay mineral by annular dark-field (ADF) STEM.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the bright contrast of the Pt atoms, the clay mineral nanosheets were observed stably and exhibited the characteristic periodic hexagonal contrast pattern of pristine clay mineral nanosheets. 21,22 These observations demonstrated that Pt atoms are a valid marker for ADF−STEM imaging of guest molecules assembled on a clay mineral nanosheet, as well as on simpler substrates such as graphene. [13][14][15] The Fourier transform (Figure 3d) corresponding to the medium magnification ADF-STEM image of the monolayer region (Figure 3c) revealed that the in-plane distance was similar to previously reported values for the (hk0) facet of montmorillonite.…”
Section: Resultsmentioning
confidence: 93%
“…Stable atomic-scale imaging of monolayer clay mineral nanosheets via ADF-STEM was recently reported for the first time by the current authors. 21,22 The present study aimed to directly image single organic molecules and supramolecular assemblies on monolayer clay mineral nanosheets using heavy metal atom markers. Electrostatic interactions are a weak non-covalent interaction, and enabled strong fixation of each organic molecule on the ionic 2D nanosheet supports.…”
Section: Introductionmentioning
confidence: 99%
“…The observed in-plane distances for 2D VMT are shown in Table S1 (Supporting Information) and consistent with the atomic structure expected for monoclinic alluminosilicates. [27,28] Energy-dispersive X-ray spectroscopy maps of 2D VMT show the presence of Si, Al, Mg, and Fe (Figure 1i). We use electron probe microanalysis to quantify four main components in VMT, namely SiO 2 , MgO, Al 2 O 3 , and FeOT, and their content is found to be 39.35 ± 1.29, 24.42 ± 0.99, 10.99 ± 1.24, and 6.63 ± 0.99 wt%, respectively (Table S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%